The Mechanical Power in Patients with Acute Respiratory Distress Syndrome Undergoing Prone Positioning Can Predict Mortality - Ko-Wei Chang; Shaw-Woei Leu; Han-Chung Hu; Ming-Cheng Chan; Shinn-Jye Liang; Kuang-Yao Yang; Li-Chung Chiu; Wen-Feng Fang; Chau-Chyun Sheu; Ying-Chun Chien; Chung-Kan Peng; Ching-Tzu Huang; et al. (Diagnostics)
Background/Objectives: Mechanical power (MP) refers to ventilator-delivered energy to the lungs, which may induce lung injury. We examined the relationship between MP and mortality in patients with acute respiratory distress syndrome (ARDS) who underwent prone positioning. Methods: This multicenter retrospective study included data on all patients admitted to the intensive care units of eight referral hospitals in Taiwan from October 2015 to March 2016, and in Chang Gung Memorial Hospital Linkou branch from January 2017 to October 2023. The data were obtained from the electronic medical records of each hospital by using a standard case report form. MP was calculated as follows: MP (J/min) = 0.098 × VT × RR × (Ppeak − 1/2 × ΔP). Results: We included 135 patients who underwent prone positioning. Among them, 28-day survivors had significantly lower MP (22.6 ± 6.5 vs. 25.3 ± 6.2 J/min, p = 0.024), MP/predicted body weight (PBW) (396.9 ± 118.9 vs. 449.3 ± 118.8 10−3 J/min/kg, p = 0.018), MP/compliance values (0.8 ± 0.3 vs. 1.1 ± 0.4 J/min/mL/cmH2O, p = 0.048) after prone positioning, and significantly lower changes in MP, MP/PBW, and MP/compliance (−0.6 ± 5.7 vs. 2.5 ± 7.4 J/min, p = 0.007; −9.2 ± 97.5 vs. 42.1 ± 127.9 10−3 J/min/kg, p = 0.010; −0.1 ± 0.3 vs. 0.2 ± 0.3 J/min/mL/cmH2O, p < 0.001, respectively). Multivariate Cox regression revealed that the change in MP/compliance (HR: 7.972, p < 0.001) was an independent predictive factor for 28-day mortality. Conclusions: In ARDS patients treated with prone positioning, MP/compliance, and change in MP, MP/PBW, and MP/compliance after prone positioning differed significantly between 28-day survivors and nonsurvivors. Further randomized controlled research is required to elucidate the potential causality of decreased MP and improved clinical outcomes.